Perancangan Prototipe Sistem Informasi Akuntansi Berbasis Web Untuk Implementasi Sak Ep Pada Koperasi Syariah Nurul Amal Bandung - Maulana, Muhammad Asril; Adi Sahputra, Eko Siswo; Ahmad Baihaqi, Egi; Bagus Saputra , Andika (Journal of Economics and Business UBS, 2025)
Cooperatives in Indonesia play a strategic role in national economic development, particularly in promoting rural economic growth and job creation. However, many cooperatives still face serious challenges in terms of governance, transparency, and financial accountability. Based on 2024 data, around 40% of the 131,617 cooperatives in Indonesia are inactive or face administrative and financial problems. These issues highlight the importance of implementing financial reporting systems that comply with applicable accounting standards. Since the issuance of the Regulation of the Minister of Cooperatives and SMEs No. 2 of 2024, all cooperatives are required to prepare financial statements based on the Financial Accounting Standards for Private Entities (SAK EP) starting January 1, 2025. This study aims to design a web-based Accounting Information System (AIS) prototype to support the implementation of SAK EP at Koperasi Syariah Nurul Amal Bandung. The research employs the System Development Life Cycle (SDLC) approach using the Waterfall model, consisting of the stages of requirement analysis, system design, implementation, and testing. The results of this study produce a web-based AIS prototype consisting of transaction, general journal, ledger, and financial report modules in accordance with the SAK EP format. The implementation of this prototype is expected to improve the efficiency, transparency, and financial accountability of cooperatives, thereby supporting good governance in line with sharia principles and the latest accounting standards.